Democracia posnacional, dos debates teóricos: Habermas, Muffe y el ‘nacionalismo funcional’ - Engelken-jorge, Marcos (Nómadas. Critical Journal of Social and Juridical Science, 2008)
Is a post-national democracy possible? How could its demos find its cohesion/articulation? Which theoretical and normative frame could grasp this post-national democracy best? This paper addresses these three questions by critically exploring two related discussions: the ones which are being held by the habermasian model of deliberative democracy with the ‘functional nationalism’ and with the agonistic model of democracy. The author will conclude that it is possible to base a post-national democracy upon a deliberative approach, but that this theoretical model has to address the problems related to the formation of certain types of subjectivities in order to become fully persuasive.
Keywords: Post-national democracy; Deliberative democracy; Agonistic democracy; Nationalism; Jürgen Habermas; Chantal Mouffe